RAFT miniemulsion polymerization using dioctyl sodium sulfosuccinate. Issue 9 (14th February 2013) - Dong, Siming; Cheng, Siqing; Zetterlund, Per B.
<x xml:space="preserve">Abstract</x> The anionic surfactant dioctyl sodium sulfosuccinate (AOT) has been shown to operate well as a surfactant in aqueous miniemulsion polymerization of styrene both for conventional radical polymerization and RAFT polymerization. AOT is generally more soluble in hydrophobic monomers than in water, and is as such rather unique for an aqueous miniemulsion system. The particle size obtained was smaller than what is customary for both conventional radical polymerization and RAFT polymerization in miniemulsion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>